A comparative study of low-fluence Q-switched neodymium-doped: yttrium aluminum garnet laser versus 15% trichloroacetic acid peel in the treatment of melasma - Venu, Sridhar; Balachandar, Sarath Chandran; Nallu, Kamalanathan; Lakshmanan, C. (International Journal of Research in Dermatology, 2019)
Background: Melasma is an acquired, circumscribed, pigmentary disorder. It is characterized by more or less symmetrically distributed, dark brown macules with well-defined geographic borders and is often resistant to treatment. The aim of our study is to compare the therapeutic efficacy of low-fluence Q-switched neodymium-doped: yttrium aluminum garnet (Qs-Nd:YAG) laser versus 15% trichloroacetic acid (TCA) peel in the treatment of melasma. Methods: Our study was an open, prospective, comparative study that included 50 melasma patients. They were then randomized into group 1 (n=25) and group 2 (n=25) by means of sequentially numbered list. Patients in group 1 were treated with 15% TCA. The procedure was repeated every two weeks for 6 times. Group 2 patients were treated with low influence Q-switched Nd:YAG laser. The treatment was given for four sittings at a gap of 3 weeks. Melasma area and severity index (MASI) was used to assess the response of therapy. Patients were followed up for 12 weeks after completing the study. Results: The total percentage of reduction in mean MASI was 41.92% in group 1 and 27.88% in group 2 which was statistically significant (p=0.007). Post inflammatory hyper- pigmentation was the most common side effect in patients treated with Nd-YAG laser, particularly Fitzpatrick skin type V. Conclusions: 15% TCA was better than Q switched Nd:YAG laser for the treatment of melasma. Qs-Nd:YAG laser is not an effective treatment option due to higher incidence of adverse effects.